Development of IPS Learning Model Based on Religious Education to Improve Knowledge Competence and Attitude - Indari; Suprijono, Agus; Wisnu, Mr (Universitas Negeri Surabaya, 2022)
This study aims to analyze the feasibility and effectiveness of the results of developing a social studies learning model based on religious education, using the Four-D Thiagarajan Model. This research reached the disseminate stage, namely the dissemination stage to the MGMP for social studies teachers in Pamekasan district. The research was conducted at Mts As-Salafiyah Sumber Duko Pakong-Pamekasan. The social studies learning model based on religious education is a representation for religion-based learning that describes the characteristics of the integration of social studies from the beginning to the end. Development is carried out on 1) Study of the potential of natural resources as religious-based material; 2) organizing learning activities refers to contextual learning; and 3) evaluation of student competency achievement authentically. Based on expert judgment, the learning model was declared suitable for use with the highest score of 89.5%. Based on the results of the calculation of the average individual completeness in the pretest of 30.4% of students declared complete and posttest of 78.2% of students declared complete. Based on these calculations there was a significant increase of 47.8%. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential.